Numerical Modeling and Computer Simulation (IntechOpen, 2021)
Information technologies have changed people’s lives to a great extent, and now it is almost impossible to imagine any activity that does not depend on computers in some way. Since the invention of first computer systems, people have been trying to avail computers in order to solve complex problems in various areas. Traditional methods of calculation have been replaced by computer programs that have the ability to predict the behavior of structures under different loading conditions. There are eight chapters in this book that deal with: optimal control of thermal pollution emitted by power plants, finite difference solution of conjugate heat transfer in double pipe with trapezoidal fins, photovoltaic system integrated into the buildings, possibilities of modeling Petri nets and their extensions, etc.